Teachers' efforts to develop entrepreneurial principles in students at UPGRIS Semarang Laboratory High School - Drifanda, Valdyan; Windrayadi, Yosia Dian Purnama (Universitas PGRI Semarang, 2023)
he curriculum transition from â€œkurikulum-13â€ to â€œKurikulum Merdekaâ€ certainly brings a new paradigm in classroom learning. There is something new in the new curriculum at the high school level, namely entrepreneurship learning which is contained in one of the P5 themes (Pancasila Student Profile Strengthening Project). This study aims to determine the efforts of teachers in developing students' entrepreneurial principles on entrepreneurial projects. This study used qualitative research methods. The source of the research data is a high school teacher from the Semarang UPGRIS Laboratory School who teaches economics subjects. The results of the study found that teachers' efforts in developing entrepreneurial principles by providing knowledge in the form of deepening students' creativity towards new product innovations, providing knowledge about strategic management, providing knowledge related to marketing management and also motivating them to always innovate and not be satisfied with the results of their business achievements.